The Holocene evolution of a sinkhole on the Southeast Red Sea Shelf: from saline palaeolake to stratified marine setting - Paraschos, Francesca; Berke, Melissa A.; Koutsodendris, Andreas; Friedrich, Oliver; Sergiou, Spyros; Geraga, Maria; Kaberi, Helen; Williams, Ross; Bailey, Geoffrey; Pross, Jörg; Sakellariou, Dimitris (Global and planetary change, 2026)
The submerged coastal landscapes of the southern Red Sea preserve key archives of postglacial environmental change, shaped by sea-level rise and shifting hydroclimatic regimes. On the southeast shelf, the Farasan Deep - a deep, morphologically isolated sinkhole - records a rare transition from a saline palaeolake to a stratified marine setting. We present a new multiproxy record from sediment core FA24, integrating lipid biomarkers (branched and isoprenoid glycerol dialkyl glycerol tetraethers [GDGTs]), XRF-core scanning, LOI, sedimentology, and micropalaeontology to reconstruct water-column structure, redox dynamics, and microbial and faunal shifts over the past 11.8 kyr. Results reveal three distinct phases. Phase I (11.8-8.7 ka) reflects hydrographic isolation, strong stratification, and sustained bottom-water anoxia. Laminated organic-rich sediments, diatom mats, low foraminiferal counts, and biomarker evidence indicate persistent oxygen depletion and a distinct microbial ecology. Phase II (8.7-6.7 ka) captures transitional dynamics, marked by episodic marine incursions, fluctuating redox conditions, rising GDGT inputs, and sporadic foraminiferal reappearances. Phase III (post-6.7 ka) signals full marine reconnection with stable stratification, persistent bottom-water anoxia, increased microbial lipid production, and benthic foraminiferal assemblages dominated by infaunal taxa. The Farasan Deep record sheds light on the timing and feedbacks of postglacial marine reconnection in marginal basins. Beyond its regional context, it provides a globally relevant analogue for redox-sensitive carbon cycling, stratification feedbacks, and GDGT proxy behavior in semi-enclosed systems. These findings further underscore the geoarchaeological significance of submerged landscapes and support improved palaeoclimate reconstructions in hydroclimatically sensitive marine settings.
Online verfügbar: 10. November 2025, Artikelversion: 15. November 2025
Gesehen am 28.01.2026